1979
DOI: 10.1002/j.2164-4918.1979.tb05417.x
|View full text |Cite
|
Sign up to set email alerts
|

The School Counselor As Consultant: A Historical Review

Abstract: This article contains a historical review of the school counselor in the role of consultant. Published articles that have appeared in four APGA journals during the past 21 years provided the basis for the review. General trends in each journal and a developmental history of the consultation movement are presented. The conclusion was that a serious gap exists between the theory and practice of consultation in schools. Specific needs must be addressed for the school counselor as consultant model to be fully real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1981
1981
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Counseling and guidance personnel in the state departments of public instruction reported that consultation accounted for approximately one-fourth of the time they spent in services offered (Hollis & Wantz, 1980). Miles and Hummel's (1979) and Kahnweiler's (1979) data, which indicated that consultation was perceived as highly important to counseling, also corroborates this trend.…”
Section: Coursessupporting
confidence: 61%
“…Counseling and guidance personnel in the state departments of public instruction reported that consultation accounted for approximately one-fourth of the time they spent in services offered (Hollis & Wantz, 1980). Miles and Hummel's (1979) and Kahnweiler's (1979) data, which indicated that consultation was perceived as highly important to counseling, also corroborates this trend.…”
Section: Coursessupporting
confidence: 61%
“…There is a need for more specific and pragmatic consultation models and techniques (Kahnweiler, 1979). Curriculum intervention through psychological education enables the school counselor to become a consultant and a facilitator by informing all staff members of the link between psychological theory and practice and the curricula and teaching methods.…”
Section: Consultationmentioning
confidence: 99%
“…Though mandates, resolutions, role definitions, models, and texts exist on consulting, techniques for consultation skill training have not followed. Kahnweiler (1979) ends his historical review of consultation theory and practice by citing the need for models and techniques that contain specific components for practitioners and trainees. Myrick (1977), Froehle (1978), and McGreevy (1978) have suggested training methods but have not included a model for trainee skill development in the consulting interview.…”
Section: Direct-a Consultation Skills Training Modelmentioning
confidence: 99%